The reproductive biology of Vatica yeechongii Saw (Dipterocarpaceae) / Suhaida Mustafa - Suhaida , Mustafa (2017)
Vatica yeechongii is a critically endangered and endemic species in Peninsular Malaysia (Chua et al., 2010). Land use change is a threat to this species as the population only exist in Sungai Lalang Forest Reserve, Selangor and Setul Forest Reserve, Negeri Sembilan. To date, there are less than 50 trees with diameter at breast height (DBH) more than 2 cm recorded from both areas. The aim of this research is to study the flowering and fruiting pattern, breeding system and potential pollinators for this species. Vatica yeechongii flowers annually but there are few trees producing flowers twice a year. Vatica yeechongii begins to produce flowers between February and March, while fruits mature and fall between July and August. The total duration period from trees started to develop flowers until mature fruits fall took about 21-22 weeks. Flower started to open at early dawn around 0530 hour and lasted for four to five hours. Vatica yeechongii is protandrous, where the anthers started to dehisce pollens upon floral opening and the stigmas become receptive 30 minutes later. Dehiscence of petals and anthers began as early as 0930 hours. V. yeechongii is an outcrosser and self-incompatible species. Insects from the family Apidae (Trigona sp.) were seen to be more effective as pollinators due to their hairy abdomens and legs which were believed to be able to carry more loads of pollens. The pollen grains are tricolpate, with thick and coarsely reticulate exine, viable for almost two days.